Action of nucleosides and nucleotides at 7 transmembrane-spanning receptors - Jacobson, Kenneth A.; Costanzi, Stefano; Kim, Soo-Kyung; Roh, Eunjoo; Joshi, Bhalchandra V.; Tchilibon, Susanna; Duong, Heng T.; Gao, Zhan-Guo (TAYLOR & FRANCIS INC, 2006)
Ribose ring-constrained nucleosides and nucleotides to act at cell-surface purine recesptors have been designed and synthesized. At the P2Y(1) nucleotide receptor and the A(3) adenosine receptor (AR) the North envelope conformation of ribose is highly preferred. We have applied mutagenesis and rhodopsin-based homology modeling to the study of purine receptors and used the structural insights gained to assist in the design of novel ligands. Two subgroups of P2Y receptors have been defined, containing different sets of cationic residues for coordinating the phosphate groups. Modeling/mutagenesis of adenosine receptors has focused on determinants of intrinsic efficacy in adenosine derivatives and on a conserved Trp residue (6.48) which is involved in the activation process. The clinical use of adenosine agonists as cytoprotective agents has been limited by the widespread occurrence of ARs, thus, leading to undesirable side effects of exogenously administered adenosine derivatives. In order to overcome the inherent nonselectivity of activating the native receptors, we have introduced the concept of neoceptors. By this strategy, intended for eventual use in gene therapy, the putative ligand binding site of a G protein-coupled receptor is reengineered for activation by synthetic agonists (neoligands) built to have a structural complementarity. Using a rational design process we have identified neoceptor-neoligand pairs which are pharmacologically orthogonal with respect to the native species.
Keywords: A(3) ADENOSINE RECEPTOR; P2Y(1) RECEPTOR; ANTAGONISTS; AGONISTS; DERIVATIVES; A(2A); SELECTIVITY; ACTIVATION; POTENT; CONFORMATION